When a State Is a Party to a Dispute – (Court-)Administrative Mediation in Poland and in Ukraine (A Comparative Perspective) - Kalisz, Anna; Serhieieva, Alina (Review of European and Comparative Law, 2023)
Ukraine’s status as a candidate country for the European Union membership reinforces the need for comparative analysis between Ukrainian regulations and the laws of other EU Member States, as well as European regulations. One of the fields of comparative law is the development of mediation as a legal institution, also in cases when the state is involved – for disputes covered by administrative law. This has already been a subject of interest and promotion of both the EU and the Council of Europe, as European standards of democracy provide for the state’s cooperation with citizens/individuals. The aim of this article is – firstly – to compare the current development of mediation in administrative and court-administrative cases in Poland and in Ukraine, the similarities in successes and challenges, and – secondly – to determine to what extent both countries follow the latest CEPEJ guidelines. Although